Landscape structural changes between 1950 and 2012 and their role in wildlife–vehicle collisions in the Czech Republic. (31st December 2016) - Keken, Z.; Kušta, T.; Langer, P.; Skaloš, J.
Abstract: Roadway safety is a major concern for the general public and understanding factors that affect wildlife–vehicle collisions (WVCs) which is an important area in road ecology research. Even though many studies on landscape change have been conducted worldwide in the last 20 years, as well as present work focused on the effects of selected landscape structural characteristics on WVCs, an effort to examine the effects of historical changes in landscape structure on WVCs is missing. The main goal of this study is to analyse the role of the spatio-temporal changes in landscape structure between 1950 and 2012 for WVCs in the Czech Republic. Aerial photos from 1950 and 2012 were used to analyse changes in landscape structure based on the use of a Geographic Information System (GIS). The analyses were conducted in 52 hotspots (areas with the highest density of WVCs per square kilometre in the Czech Republic). The results showed that each hotspot has had a relatively high reconfiguration of the landscape structure, which has had a crucial influence on the given habitats. In some hotspots the level of unstable land cover patches between 1950 and 2012 was more than 80% of the total area and the average of the unstable patches for all 52 hotspots was 53.23%. The identification of transformation trajectories is also very important, i.e. on the one hand huge decreases of grassland, and on the other hand increasing successional areas, arable land, and built-up area, as well as areas of transport infrastructure. The landscape pattern was dramatically changed, too. A fine, heterogeneous mosaic of small patches (with many possibilities for migration pathways) was converted into large, homogeneous blocks. In some cases a highly complex structure was created, where two or more roads follow similar directions. All this activity has resulted in low landscape permeability and a higher risk of WVCs. A retrospective view on landscape can help to correct this state of affairs.